Degradasi kualitas fisis air Danau Maninjau terhadap variasi jarak dan jumlah keramba (Degradation of the physical quality of water in Lake Maninjau with variations in distance and number of cages) - Puput Mulya Sari; Yenni Darvina; - Hamdi (Department of Physics – Universitas Negeri Padang UNP, 2015)
The purpose of this research are to analys physical quality (temperature, pH, electrical conductivitas, turbiditas, and concentrasion of lead) at Maninjau Lake. Maninjau Lake has problem die of fish and make harm farmer of keramba. This research use variation of distance 0 m, 5 m and 10 m and three locations Bayua, Koto Gadang and Sigiran. The standart for physical quality, temperature 23-30 oC use Thermometry, turbiditas <5 NTU use Turbidimetry, pH 6-9, electrical conductivitas <250 µS/cm use Conductivity Metry and then concentration of Lead <0,03 mg/l use AAS. The result Bayua has worse the physical quality (temperature 31,0 oC, pH 5,6, electrical conductivitas 125,2 µS/cm, turbiditas 5,1 NTU, Lead 0,954142 mg/l). While Koto Gadang (temperature 29,5 oC, pH 7,1, conductivitas 123,1 µS/cm, turbiditas 4,8 and concentrasion of lead 0,3778 mg/l) has worse the physical quality than Sigiran (temperature 27,5 oC, pH 7,5, conductivitas 99,7 µS/cm, tur